LE DÉVELOPEMENT DU MEDIA D’EVALUATION INTERACTIVE COMME L’EXERCICE DE LA COMPREHENSION ORALE POUR LES LYCEENS DE DOUZIEME ANNÉE - Kholifah, Insiana Nazilatul; Suâ€™udi, Astini; Syaefudin, Mohamad (Didacticofrancia: Journal Didactique du FLE, 2014)
Les élèves de la classe XII  ont toujours la difficulté pour comprendre le document sonore. Selon l’observation durant la pratique sur terrain, le professeur lisait seulement le texte se trouvant dans le cahier d’exercice. La raison était le manque de média. Pourtant le lycée a le web permettant les professeur de mettre leur ressources pédagogiques et les élèves peuvent télécharger et apprendre  individuellement. Il est donc important de créer un média pour aider les lycéens de s’exercer la compréhension orale.  L’objectif de cette recherche est de créer un exercice interactif de la compréhension orale. La recheche a utilisé le research and development adoptant cinq étapes, ce sont l’analyse des problèmes, la collection de data, le plan du produit, la validation du produit, et la revision du produit. Le contenu de média a référé à la matière de la classe XII. Les thèmes de ce média sont: le sport, la musique, les vacances et le transport. Chaque thème a dix questions. Le résultat de cette recherche est les exercices interractifs de compéhension orale pour les lycéens de la classe  XII.  XIIth  grade students on average still have difficulty in understanding the French language listening. Based on observations during practice in the field, teachers teach by read the discourse contained in the student worksheet. Although there is a school that has a web that allows teachers to create the media and upload it, so students can download it to learn individually, but the media uploaded is limited. Therefore, the media need to be made to help students practice and measure their own abilities in French language listening skills. The purpose of this reseach is produce a listening evaluation tool interctive for XIIth grade. The student is expected to learn by themselves at home, to evaluate their understanding ability of the French language skills through listening skills. This research use research and development procedures. Only five steps used on this research because of the limited time to do other steps. They are problem and potential analysis, data collection, product design, validation of the design, and design revisions. The contents of the media training tailored to the class XII material. But not all themes included in this training media. There are only three themes that will be used   in   the   media   exercise.   They   are   sports   and   music,   holidays,   and transportation. There are 10 questions contained on each theme. The result of this research is a listening evaluation tool interactive for XIIth grade.